Backbone 1H, 15N, and 13C Resonance Assignment and Secondary Structure Prediction of HP1298 from Helicobacter pylori - 김원제; 임종수; 손우성; 안희철; 이봉진 (한국자기공명학회, 2008)
HP1298 (Swiss-Prot ID ; P65108) is an 72-residue protein from Helicobacter pylori strain 26695. The function of HP1298 was identified as Translation initiation factor IF-1 based on sequence homology, and HP1298 is included in IF-1 family. Here, we report the sequence-specific backbone resonance assignments of HP1298. About 97% of all the 1HN, 15N, 13Cα, 13Cβ, and 13CO resonances could be assigned unambiguously. We could predict the secondary structure of HP1298, by analyzing the deviation of the 13Cα and 13Cβ shemical shifts from their respective random coil values. Secondary structure prediction shows that HP1298 consists of six β-strands. This study is a prerequisite for determining the solution structure of HP1298 and investigating the structure-function relationship of HP1298 . Assigned chemical shift can be used for the study on interaction between HP1298 and other Helicobacter pylori proteins.